Implementation of Remote Auditing Reduces Skepticism and Reward of Auditor Staff in Public Accounting Firm - Arsyfi, Moh. Syahrul Nur; Arifin, Johan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research seeks to determine the application of remote auditing to professional skepticism and rewards for auditor staff at KAP X in Yogyakarta. This research methodology uses the discipline comparative method. The research informants consist of 3 auditor staff. The research results reveal that the implementation of remote auditing has not completely reduced auditors' professional skepticism but has reduced auditor staff rewards. Auditor competency and experience are the main keys to implementing remote working. Implementing remote auditing can make audit implementation more efficient and effective. Remote auditing is used as an alternative practice for carrying out audits at KAP. This research takes a deeper look at the skepticism and rewards of auditor staff in implementing remote auditing at small KAPs in Yogyakarta in the transition to the end of the COVID-19 pandemic.